Acupuncture reduces cocaine psychomotor responses by activating the rostromedial tegmental nucleus. (10th May 2021) - Chang, Suchan; Fan, Yu; Lee, Soo Min; Ryu, Yeonhee; Lee, Bong Hyo; Kim, Sang Chan; Bills, Kyle B.; Steffensen, Scott C.; Yang, Chae Ha; Kim, Hee Young
Abstract: The rostromedial tegmental nucleus (RMTg), a GABAergic afferent to midbrain dopamine (DA) neurons, has emerged as an integral player in both rewarding and nociceptive responses. While previous studies have demonstrated that acupuncture modulates DA transmission in the mesolimbic reward system originating in the ventral tegmental area (VTA) and projecting to the nucleus accumbens (NAc) and can reduce drug self‐administration, the central links between peripheral acupuncture signals and brain reward systems are not well‐characterized. Thus, we hypothesised that acupuncture would elicit inhibitory signals from RMTg neurons to brain reward systems. Acupuncture reduced acute cocaine‐induced locomotor activity and DA release in a point‐specific manner, which was blocked by optogenetic silencing or chemical lesion of the RMTg. The acupuncture effect was mimicked by chemical activation of the RMTg. Acupuncture activated RMTg GABA neurons. In addition, the inhibitory effects of acupuncture on acute cocaine‐induced locomotor activity were prevented by electrolytic lesions of the lateral habenula (LHb) or fasciculus retroflexus (FR), areas known to project to the RMTg. These findings suggest that acupuncture recruits the RMTg to reduce the psychomotor responses enhanced by acute cocaine. Abstract : While acupuncture is widely practiced for treating drug addiction, the central links between peripheral acupuncture signals and brain reward systems are not well‐characterized. Here we show that acupuncture activates rostromedial tegmental (RMTg) GABA neurons and reduces cocaine psychomotor responses, cocaine‐induced NAc DA release via activation of RMTg and optogenetic inhibition or activation of habenula‐RMTg circuits modulates the acupuncture effect. These results suggest that acupuncture activates habenula‐RMTg circuits and suppresses cocaine addictive behaviours.